2009
DOI: 10.1053/j.gastro.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Treatment of Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis, a recently recognized and growing clinical disorder over the past decade, is characterized by antigen-driven eosinophil accumulation in the esophagus. Symptoms frequently mimic those of gastroesophageal reflux disease (GERD) but the two diseases are quite distinct in terms of their histopathology, genetic signature, response to therapy, hereditary risk and association with allergy. Disease pathogenesis involves the interplay of external and genetic factors, particularly food antigens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
212
0
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(231 citation statements)
references
References 136 publications
3
212
0
14
Order By: Relevance
“…It may also affect the level of activation-induced cytidinedeaminase (AID) and induce the colon inflammation as well as transformation into cancer cells (Endo et al, 2008). Moreover, IL-13 influences eosinophils and cause their prolonged survival, activation, and migration to inflammatory lesions (Rothenberg, 2009). Data show that IL-13 receptors are highly expressed in colonic epithelial cells.…”
Section: Introductionmentioning
confidence: 89%
“…It may also affect the level of activation-induced cytidinedeaminase (AID) and induce the colon inflammation as well as transformation into cancer cells (Endo et al, 2008). Moreover, IL-13 influences eosinophils and cause their prolonged survival, activation, and migration to inflammatory lesions (Rothenberg, 2009). Data show that IL-13 receptors are highly expressed in colonic epithelial cells.…”
Section: Introductionmentioning
confidence: 89%
“…Genetic susceptibility may play a role. Rothenberg et al associated a gene locus (5q22) to the disease (23,24) . In our study, two patients were from the same family.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features described by our study are similar to those reported elsewhere, with predominance of males (78.6%), as well as frequent abdominal pain, vomiting, failure to thrive and regurgitation, symptoms that resemble gastroesophageal reflux disease (GERD) (11,27) . Furthermore, EoE is a immunologically-mediated disease, and most patients present evidence of food allergy and/or atopy (7,24) . In the present study, 85.7% had history of atopy, more than the 68% that was reported elsewhere (27) .…”
Section: Discussionmentioning
confidence: 99%
“…107 Therefore avoidance of food antigens would be an important therapeutic strategy for EoE. There are three strategies for dietary approach in EoE; elemental diet, targeted elimination diet (after allergic testing) and six food elimination diet (SFED).…”
Section: Dietary Therapymentioning
confidence: 99%